Partnering and parenting transitions associate with changing smoking status: a cohort study in young Australians - Tian, J; Gall, S; Patton, G; Dwyer, T; Venn, A (Springer International Publishing, 2017)
To examine the effects of partnering and parenting transitions on smoking continuity in young adults.A prospective cohort study was conducted involving 1084 young smokers and former smokers who completed questionnaires at baseline (2004-2006, aged 26-36 years) and 5 years later.233/570 (40.9%) smokers quit and 58/514 (11.3%) former smokers resumed smoking during follow-up. For partnering transitions, compared with remaining not partnered, the likelihood of quitting was higher among men who became (RR 2.84 95% CI 1.62, 4.98) or stayed (RR 2.12, 95% CI 1.18, 3.80) partnered and women who became partnered (RR 1.50, 95% CI 1.03, 2.18). People who became (RR 0.14, 95% CI 0.03, 0.58) or stayed (RR 0.51, 95% CI 0.27, 0.95) partnered had a lower risk of resuming smoking than their continuously not partnered peers. For parenting transitions, having a first child born increased women's probability of quitting smoking relative to remaining childless (RR 1.74, 95% CI 1.30, 2.33), while having additional children did not.The benefits of partnering were greater for men than women and transition into parenthood was of greater benefit to women.